Decision-making styles as predictors of career decision difficulties in secondary school students with regard to gender - Pečjak, Sonja (Array, 2019)
The study aimed to examine whether students' different career decision styles predict their difficulties in deciding about their future education. We measured students' adaptive self-confident and three maladaptive decision-making styles: avoidant, panic, and impulsive, and examined how these styles are related to students' difficulties in career decision-making: internal and external conflicts, lack of information, and dysfunctional beliefs. Our sample comprised 792 final-year students from 26 Slovenian secondary schools. We used the Career Decision Difficulties Questionnaire (CDDQ) and Adolescent Decision Making Questionnaire (ADMQ), which we adapted to the Slovenian language. The results showed that boys use self-confident and impulsive decision-making styles more often and panic decision-making style less often than girls do. Boys reported less internal conflicts, lack of information and dysfunctional beliefs. Among CDDQ scales, we found a strong correlation between Internal Conflicts and Lack of Information scale scores and moderate correlations of these two scales with External Conflicts. Correlations between ADMQ scales were low to moderate: Self-Confident Style scale score correlated negatively with scores on scales of all three maladaptive styles. The Lack of Information score was best predicted by the Panic Decision-Making Style score, the External Conflicts score by the Panic and Impulsive Decision-Making Style scores, and the strongest predictors of Dysfunctional Beliefs score was the Panic Decision-Making Style score. Having more pronounced panic style and being a girl turned out to be related to more difficulties in all domains of career decision-making. Some practical career counselling implications of these findings are discussed.